(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Joints study in Skhaba region shows the existence two joint directions, principal dominant NW-SE Joints from extension origin upper Cretaceous age, unrelated and older than faults in studied area statistically, the presence of Calcareous filling in the joints that is supported the extension origin in the first phase. Secondary NE-SW joints from Miocen-Pliocen in age, and from extension origin ,related to the formation of faults, most of them contain thin iron crust in secondary phase.